Nucleosome remodeling and transcriptional repression are distinct functions of Isw1 in Saccharomyces cerevisiae. - Pinskaya, M; Nair, A; Clynes, D; Morillon, A; Mellor, J (2009)
The SANT domain is a nucleosome recognition module found in transcriptional regulatory proteins, including chromatin-modifying enzymes. It shows high functional degeneracy between species, varying in sequence and copy number. Here, we investigate functions in vivo associated with two SANT motifs, SANT and SLIDE, in the Saccharomyces cerevisiae Isw1 chromatin-remodeling ATPase. We show that differences in the primary structures of the SANT and SLIDE domains in yeast and Drosophila melanogaster reflect their different functions. In yeast, the SLIDE domain is required for histone interactions, while this is a function of the SANT domain in flies. In yeast, both motifs are required for optimal association with chromatin and for formation of the Isw1b complex (Isw1, Ioc2, and Ioc4). Moreover, nucleosome remodeling at the MET16 locus is defective in strains lacking the SANT or SLIDE domain. In contrast, the SANT domain is dispensable for the interaction between Isw1 and Ioc3 in the Isw1a complex. We show that, although defective in nucleosome remodeling, Isw1 lacking the SANT domain is able to repress transcription initiation at the MET16 promoter. Thus, chromatin remodeling and transcriptional repression are distinct activities of Isw1.